Patterns of morphological and genetic variation in the Mentocrex kioloides complex (Aves: Gruiformes: Rallidae) from Madagascar, with the description of a new species - Goodman, Steven M.; Raherilalao, Marie Jeanne; Block, Nicholas L. (Zootaxa, 2011)
We examine patterns of morphological and molecular genetic differentiation in the endemic Mentocrex kioloides complex of Madagascar. This forest-dwelling rail (often placed in Canirallus) is known from two subspecies: M. k. kioloides, which occurs in the island’s humid central and eastern forests; and M. k. berliozi, which occurs in the transitional dry deciduoushumid forests of the northwest. Two new specimens (an adult and a downy young) recently became available from limestone karst areas of the lowland central west, the adult of which is notably different in size and plumage coloration, as well as showing considerable genetic divergence, from the two recognized subspecies of M. kioloides. The central west animals are herein named as a species new to science, Mentocrex beankaensis, sp. nov.